2014
DOI: 10.1177/2151458514537272
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Preoperative Frailty Utilizing Validated Geriatric Mortality Calculators and Their Association With Postoperative Hip Fracture Mortality Risk

Abstract: Overall, the VASQIP 30-day and MMRI-R 6-month mortality calculators showed significant differences in mortality risk between survivors versus nonsurvivors in a population with hip fracture. In contrast, the Four-Year Mortality calculator may not sufficiently discriminate operative risk. The easily obtained MMRI-R has the potential to provide information on short-term postoperative mortality risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…18 Similar findings have been reported in other ACS-NSQIP-based studies for emergent general operation, vascular, and orthopedic procedures. 1,[19][20][21] In a prospective cohort of 325 patients >65 years of age undergoing emergent general surgical procedures, Hewitt et al 10 noted an increased mortality in frail patients. However, the sample size in smaller institutional studies was inadequate to determine the association between frailty and mortality.…”
Section: Discussionmentioning
confidence: 98%
“…18 Similar findings have been reported in other ACS-NSQIP-based studies for emergent general operation, vascular, and orthopedic procedures. 1,[19][20][21] In a prospective cohort of 325 patients >65 years of age undergoing emergent general surgical procedures, Hewitt et al 10 noted an increased mortality in frail patients. However, the sample size in smaller institutional studies was inadequate to determine the association between frailty and mortality.…”
Section: Discussionmentioning
confidence: 98%
“…We have validated the assessment tool retrospectively and prospectively with local quality data. [16][17][18] In addition, the purpose of our paper was not to repeat a univariate/multivariate study as has been performed previously but rather to emphasize the ability of an easily administered frailty tool to identify high-risk patients undergoing CEA in a large database and its potential applicability to daily practice.…”
Section: Discussionmentioning
confidence: 99%
“… 2 – 4 The risk of mortality in an elderly individual 3 months after hip fracture is greater than 4 times that of one without, and the risk of death at 1 year is twice that of a comparable uninjured person, 3 , 5 , 6 and studies have demonstrated that decreased preoperative function is predictive of increased postoperative morbidity and mortality, emphasizing the importance of improved postoperative cognition and exercise for maximizing functional outcome after a hip fracture. 7 , 8 Estimates of total cost to the health care system for hip fractures, including both hospital and posthospital care, are up to US$30 billion annually in the United States. 2 , 4 , 9 – 11 Despite increased emphasis on bone health, given the rapidly increasing elderly populace, the associated costs of hip fracture care are only expected to continue to rise.…”
Section: Introductionmentioning
confidence: 99%